2009
DOI: 10.1364/oe.17.006118
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturization of zoom lenses with a single moving element

Abstract: We present an analysis of single-moving-element zoom lenses in the thin-lens limit and show how the length of these zoom lenses is determined by the zoom-factor, sensor-dimension and the depth-of-focus. By decreasing the sensor size and extending the depth-of-focus, the lengths of these zoom lenses can be reduced significantly. As an example we present a ray-traced design of a miniaturized single-moving-element zoom lens with a 2.3 x zoom-factor and show how the exploitation of modern miniaturized detector arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The proper choice for V1 and V2 improves the quality of the restored images of a given optical system in terms of focal range, signal to noise ratio and maximum spatial frequency, among other parameters [4,20,21]. Thus, controlled rotation of these elements will suffice in optimizing the system if conditions or performance demands change, as for instance, change in zoom lenses from infinite conjugate imaging to finite conjugate imaging [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proper choice for V1 and V2 improves the quality of the restored images of a given optical system in terms of focal range, signal to noise ratio and maximum spatial frequency, among other parameters [4,20,21]. Thus, controlled rotation of these elements will suffice in optimizing the system if conditions or performance demands change, as for instance, change in zoom lenses from infinite conjugate imaging to finite conjugate imaging [6].…”
Section: Methodsmentioning
confidence: 99%
“…One clear example of the need for this hybrid solution is the control of thermally induced aberrations in IR imaging systems due, for instance, to the dramatic change in the refractive index of commonly used materials such as germanium as well as other geometrical and mechanical changes in optical set-ups. A recent application for zoom lenses is another example of the potential applicability of the method [6].…”
Section: Introductionmentioning
confidence: 99%
“…The seminal 1995 paper by Dowski and Cathey [2] showed that a cubic optical phase function introduced into the exit pupil of an imaging system yields a point-spread function (PSF) that is approximately invariant to defocus, exhibits no nulls in the MTF, and therefore enables digital recovery of a high-quality image for an extended DOF [3]. Control of focus-related aberrations is a major challenge in lens design, and so hybrid imaging using cubic or other antisymmetric phase functions such as trefoil [4] has been exploited for simplification of lens design and manufacture in miniaturization of zoom lenses [5] and thermal imaging [6], particularly for infinite-conjugate imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Many applications may benefit from extended DOF capabilities in macroscopic imaging, for example in surveillance, machine vision or biometrics problems where the DOF extension is a clear advantage [2,3]; but the technique can also be used to reduce system complexity [4] or for athermalisation and achromatisation of infrared imaging systems [5].…”
Section: Introductionmentioning
confidence: 99%